Manusia dalam Proyek Kekekalan: Sebuah Studi Teologis tentang Rencana Ilahi, Pembentukan Karakter, dan Arah Eskatologis - Peiter Jeckson Tomasoa; Daud Manno (SAINT PAUL'S REVIEW, 2026)
This article explores the theological interconnection between divine providence, character formation, and eschatological orientation in the life of believers. Employing a systematic theological and thematic synthesis approach, the study asserts that Christian character is inseparable from God's eternal project. Character is not merely moral behavior, but a spiritual response to divine providence and preparation for eternal life. By placing Jesus Christ as the model and standard of perfect character, the study demonstrates that character formation is a transformational process shaped by Scripture, the Holy Spirit, suffering, and hope in the world to come. The study contributes to the development of spiritual theology, faith formation policy, and character-based ministry in society.